PENGOLAHAN SAMPAH DENGAN TEKNIK LANDFILL DI TPA SARIMUKTI YANG MERUSAK LINGKUNGAN SUNGAI WALUNGAN CIPICUNG DESA SARIMUKTI - Zakiyatuddin, Qois; Undiana, Nala Nandana; Sarbeni, Irwan (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2023)
The explosion of the Leuwigajah Landfill in 2005 caused the transfer of the landfill to Sarimukti, a resident of the village Sarimukti was forced to give up his profession, which was originally a farmer and a trader, now they become scavengers. Because more promising income can also be done at any time. Although there are those who earn a little depending on the hours and results of garbage. The author wants to reveal about management Sarimukti Landfill waste which is increasingly in the media and public attention. It also reveals many facts and data related to management as well as the inhibiting factors for the disposal process at the Sarimukti Landfill. The processing technique used by Sarimukti Landfill still uses landfill techniques, namely dumping and stockpiling. Because the garbage overload at the Sarimukti landfill has disrupted the environment, one of which is the Walungan Cipicung River. Wastewater from garbage makes the river unusable for the residents of Sarimukti Village.